2013
DOI: 10.1007/978-1-62703-363-3_22
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Skin Substitutes

Abstract: Bioengineered skin has great potential for use in regenerative medicine for treatment of severe wounds such as burns or chronic ulcers. Genetically modified skin substitutes have also been used as cell-based devices or "live bioreactors" to deliver therapeutics locally or systemically. Finally, these tissue constructs are used as realistic models of human skin for toxicological testing, to speed drug development and replace traditional animal-based tests in a variety of industries. Here we describe a method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In this respect, the ability to emulate in a cell culture the physical cues involved in the physiological development of a normal cardiac tissue is a key for a successful application of tissue engineering in regenerative medicine. Although bioengineered tissues such as skin [3] and bone [4] are already a clinical option available to patients, cardiac muscle tissue engineering is a present challenge in biomedical research—albeit several studies witness a definite advancement in this field [5]. …”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the ability to emulate in a cell culture the physical cues involved in the physiological development of a normal cardiac tissue is a key for a successful application of tissue engineering in regenerative medicine. Although bioengineered tissues such as skin [3] and bone [4] are already a clinical option available to patients, cardiac muscle tissue engineering is a present challenge in biomedical research—albeit several studies witness a definite advancement in this field [5]. …”
Section: Introductionmentioning
confidence: 99%
“…These biomaterials can create an appropriate environment for cell proliferation, differentiation, migration, and gene expression. These natural scaffolds can support angiogenesis due to their notable cell affinity and their ability to provide a microenvironment similar to the extracellular matrix . Decellularized constructs have been used for skin transplantations, cosmetic surgery, and for skin defects, and the results have confirmed that they can support skin regeneration after implantation .…”
Section: Introductionmentioning
confidence: 99%
“…These natural scaffolds can support angiogenesis due to their notable cell affinity and their ability to provide a microenvironment similar to the extracellular matrix. [17] Decellularized constructs have been used for skin transplantations, cosmetic surgery, and for skin defects, and the results have confirmed that they can support skin regeneration after implantation. [18,19] Decellularized scaffolds can stimulate important biological processes such as reepithelialization, granular tissue formation, and neovascularization at the initial stages of implantation.…”
Section: Introductionmentioning
confidence: 99%